Finanças pessoais: um comparativo entre acadêmicos de Educação Física de duas instituições da cidade de Manaus - Brelaz, Lukas de Carvalho (Brasil, 2023)
The personal finance management is a very common topic in the area of social sciences. However, it is a need that should also reach professionals in other areas, such as health area, for example. In the case of Brazil, the collection of academic research related to personal finance is still very scarce, and it is no different for students of Physical Education course, who in their curricular series do not even require the knowledge of financial education for admission. The objective of this work was to identify the differences in the management of personal finances among Physical Education students from Higher Education Institutions, one from a Public Institute and the other one from a Private Institute. It was found that Physical Education students in general have a low degree of financial education and still seek to achieve their financial independence. It’s concluded that Public Institute academics have the habit of managing their finances in a more controlled manner while looking for new sources of income, being concerned about paying their bills and help financially at home, while Private Institute academics have socioeconomic characteristics that would enable them to better manage their finances, but they end up preferring to settle down, in addition to having a more impulsive buying behavior.